Tumors: Wounds That Do Not Heal—A Historical Perspective with a Focus on the Fundamental Roles of Increased Vascular Permeability and Clotting - Dvorak, Harold F. (Seminars in Thrombosis and Hemostasis, 2019)
Similarities between solid tumor stroma generation, wound healing, chronic inflammation, and associated inflammatory diseases have prompted interest from the time of Virchow. However, it was not until the 1970s that these entities were shown to share important molecular mechanisms. Foundational to all of them is the initiating role of vascular endothelial growth factor (VEGF-A) in increasing vascular permeability to plasma and plasma proteins. Extravasated plasma activates the tissue factor clotting pathway, leading to extravascular deposition of a fibrin gel. Fibrin serves initially as a provisional stroma that provides a favorable substrate for the attachment and migration of tumor cells, as well as host fibroblasts, endothelial, and inflammatory cells. Fibrin and its degradation products have proangiogenic activity with important roles in the generation of new blood vessels and connective tissue stroma. Over time, fibrin is degraded and replaced by vascular and subsequently by dense, relatively avascular collagenous connective tissue, the end-product referred to as desmoplasia in tumors and scar in healed wounds. Fibrin and the mature stroma that replaces it provide a diffusion barrier to chemotherapy and a structural barrier that inflammatory cells must cross to reach tumor cells. Plasma solutes of varying size cross the endothelial cells lining capillaries and venules of normal tissues and “mother” vessels of tumors and wounds by different anatomical pathways. VEGF-A levels fall back to normal as wounds heal but remain perpetually elevated in solid tumors. Thus, tumors may heal centrally but continually initiate new healing activity as they grow and invade surrounding normal tissues.
Keywords: angiogenesis; chronic inflammation; clotting; fibrin; vascular permeability; VPF/VEGF-A; wound healing